2007
DOI: 10.1007/s11483-007-9039-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Shear Rheology of Concentrated Tomato Products. Effect of Particle Size and Time

Abstract: Time-dependent rheological properties of three tomato paste suspensions in the concentration range of 200-1,000 g paste/kg suspension have been investigated by using the vane geometry at shear rates g Á < 10 s À1 . Creep tests were conducted to analyze the influence of the level of stress on the rheological behavior of the samples before and after homogenization. The experimental results indicate that the suspensions exhibit an elastic behavior at long times and relatively low stresses, which proves that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 35 publications
(40 reference statements)
13
56
0
Order By: Relevance
“…Viscosity behavior of homemade tomato sauce is different from commercial sauce; which may be due to viscoelastic properties of tomato products, as they are primarily related to average volumetric diameter and insoluble solids content in tomato paste. The solids content is controlled by the tomato variety and processing conditions [10,17]. Furthermore, it has been shown that thermal pre-treatment of tomatoes caused the breaking of lycopene chains (natural polymer found in tomatoes) into smaller chains of isoprene [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Viscosity behavior of homemade tomato sauce is different from commercial sauce; which may be due to viscoelastic properties of tomato products, as they are primarily related to average volumetric diameter and insoluble solids content in tomato paste. The solids content is controlled by the tomato variety and processing conditions [10,17]. Furthermore, it has been shown that thermal pre-treatment of tomatoes caused the breaking of lycopene chains (natural polymer found in tomatoes) into smaller chains of isoprene [19].…”
Section: Resultsmentioning
confidence: 99%
“…However such characterizations are rare in the literature for tomato products [8][9][10][12][13][14][15][16]. The rheological properties of tomato products depend on several number of parameters, such as agronomic parameters (variety and maturity), compositional parameters (soluble solids, acidity and pectin content) and process parameters (finished product appearance and heat treatment) [13,17].…”
Section: Shear Rate Effect On the Viscosity Of Homemade And Commerciamentioning
confidence: 99%
See 1 more Smart Citation
“…The viscoelastic behaviour of plant foods suspensions of tomato, carrot, broccoli, potato and apple have been studied by many researchers (Alvarez, Fernández & Canet 2004;Bayod et al 2007;Bayod & Tornberg 2011;Bengtsson & Tornberg 2011;Day et al 2010b;Den Ouden & Van Vliet 1997;Tanglertpaibul & Rao 1987). At high particle concentration all these plant food suspensions show solid-like behaviour where G´ > G˝, show shear thinning behaviour and have a yield stress.…”
Section: Rheological Behaviour Of Plant Based Suspensionsmentioning
confidence: 99%
“…However, the impact of processing techniques on the cell wall structure depends on the type of fruit or vegetable Redgwell, Curti & Gehin-Delval 2008). Research on tomato based products has shown that reducing the particle size using homogenisation increased the yield stress and viscosity of tomato paste (Bayod et al 2007;…”
Section: Complexity In Characterising Texture Modified Foods To Gain mentioning
confidence: 99%